Red cell distribution width and red cell distribution width to total serum calcium ratio as predictors of mortality in acute pancreatitis: a retrospective cohort study - Bedel, Cihan; Türkoğlu, Sefa (The European Research Journal, 2020)
Objectives: We investigated whether red cell distribution width (RDW) and red cell distribution width to total serum calcium (RDW-to-TSC) ratio were associated with mortality in patients with acute pancreatitis (AP).Methods: A total of 170 patients who present emergency department  between January 2017 and June 2018 with a diagnosis of AP were enrolled in this study. A comparison between survivor and nonsurvivor AP patients was performed. Diagnosis of AP were defined according to the revised Atlanta classification 2012. Variables evaluated included demographics, hospital stay, laboratorial parameters and mortality.Results: AP related in-hospital mortality was 6.4%. Red cell distribution (RDW), white blood cell (WBC), platelet, serum glucose and RDW-to-TSC ratio were associated with AP mortality. RDW-to-TSC ratio had the highest AUC (0.88; 95% CI, 0.756-1.0), followed by RDW, serum glucose, platelet and WBC (AUC = 0.801, 0.797, 0.743 and 0.687 respectively). A cut-off value of RDW-to-TSC ratio >2.0, the highest sensitivity (91.9%), specificity (81.1%), PPV (82.9%), and NPV (91.1%) were achieved for prediction of AP related in-hospital mortality in approximately 86.5% of the cases (p < 0.001). Conclusions: RDW and TSC are  simple, inexpensive routine serum parameters, provided in a complete blood count test and available at admission. This study showed that RDW > 16.6 and RDW-to-TSC > 2.0 were very good predictors for AP mortality.